Pacific Crossings: Oceania and the Circulation of Literature in the 19th Century. Issue 5 (May 2014) - Macleod, Jock; Ellison, David
Abstract One consequence of increased European colonialism in the Pacific in the 19th century was a major growth in the circulation of literature, first from the colonial homelands and later from the colonies as well. This article introduces a cluster of three articles on the circulation of literature in the Pacific in the 19th century. It suggests that the elements that make up the 'communications circuit' for any publication change according to time, place and Imperial culture. Consequently, how we understand the circulation of literature in the Pacific depends on what aspect of the communication circuit we focus on, what time‐frame is at issue, and what part of the Pacific we are studying. The three articles that follow exemplify three different aspects of the communications circuit at three different moments in the 19th century Pacific. Acting as a cluster, they offer different but related perspectives on the circulation of literature in the Pacific in the 19th century.